Pengaruh Etika Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pt. Jasamarga (Persero), Tbk. Cabang Jagorawi - Agustina Massora (Fakultas Ekonomi Universitas Borobudur, 2016)
This study aims to determine the effect of the job ethic, organization commitment, and performance either partially or simultaneously at PT. Jasa marga Persero. Total population in the study is a quantitative method. Total population in this human development resourch and the study sample research, counted as many as 109 respondance. The sampling technique using purposive sampling. The variable in this study is the independent variable (independent) consisting of work ethic, organization commitment, and performance and the dependent variable (dependent) is Audit quality.The results showed that the work ethic, organization commitment, and performance effecting significant partially on Performance. work ethic, organization commitment, and performance effecting significant Simultaneously, work ethic, organization commitment and performance effecting significant effect on performance level determination coefficient to 78,2%.